Is there an uncanny valley of virtual animals? A quantitative and qualitative investigation. Issue 111 (March 2018) - Schwind, V.; Leicht, K.; Jäger, S.; Wolf, K.; Henze, N.
Highlights: Explicit investigation of the uncanny valley using virtual animals. Findings of two studies investigating the effects of realism, stylization, and emotion using a virtual cat. Quantitative and qualitative insights of potential uncanny effects using non-human characters. Abstract: Approaching a high degree of realism, android robots, and virtual humans may evoke uncomfortable feelings. Due to technologies that increase the realism of human replicas, this phenomenon, which is known as the uncanny valley, has been frequently highlighted in recent years by researchers from various fields. Although virtual animals play an important role in video games and entertainment, the question whether there is also an uncanny valley for virtual animals has been little investigated. This paper examines whether very realistic virtual pets tend to cause a similar aversion as humanlike characters. We conducted two empirical studies using cat renderings to investigate the effects of realism, stylization, and facial expressions of virtual cats on human perception. Through qualitative feedback, we gained deeper insight into the perception of realistic computer-generated animals. Our results indicate that depicting virtual animal-like characters at realism levels used in current video games causes negative reactions just as the uncanny valley predicts for humanlike characters. We conclude design implication to avoid that sensation and suggest that virtual animals should either be given a completely natural or a stylized appearance. We propose to further examine the uncanny valley by the inclusion of artificial animals.